A Simple-to-Perform ifn-γ mRNA Gene Expression Assay on Whole Blood Accurately Appraises Varicella Zoster Virus-Specific Cell-Mediated Immunity After Allogeneic Hematopoietic Stem Cell Transplantation - Boccard, Mathilde; Conrad, Anne; Mouton, William; Valour, Florent; Roure-Sobas, Chantal; Frobert, Emilie; Rohmer, Barbara; Alcazer, Vincent; Labussière-Wallet, Hélène; Ghesquières, Hervé; Venet, Fabienne; Brengel-Pesce, Karen; et al. (Frontiers in Immunology, 2022)
Herpes zoster, which is due to the reactivation of Varicella zoster virus (VZV), is a leading cause of morbidity after allogeneic hematopoietic stem cell transplantation (allo-HSCT). While cell-mediated immunity (CMI) is critical to inhibiting VZV reactivation, CMI is not routinely assessed due to a lack of reliable tests. In this study, we aimed to evaluate VZV-specific CMI among allo-HSCT recipients (n = 60) and healthy individuals (HI, n = 17) through a panel of three immune functional assays after ex vivo stimulation by VZV antigen: quantification of (i) IFN-γ release in the supernatants, (ii) T-cell proliferation after a 7-day stimulation of peripheral blood mononuclear cells (PBMC), and (iii) measurement of the ifn-γ mRNA gene expression level after 24 h of stimulation of a whole-blood sample. VZV responsiveness was defined according to IFN-γ release from VZV-stimulated PBMC. Upon VZV stimulation, we found that allo-HSCT recipients at a median time of 6 [5-8] months post-transplant had lower IFN-γ release (median [IQR], 0.34 [0.12–8.56] vs. 409.5 [143.9–910.2] pg/ml, P <.0001) and fewer proliferating T cells (0.05 [0.01–0.57] % vs. 8.74 [3.12–15.05] %, P <.0001) than HI. A subset of allo-HSCT recipients (VZV-responders, n = 15/57, 26%) distinguished themselves from VZV-non-responders (n = 42/57, 74%; missing data, n = 3) by higher IFN-γ release (80.45 [54.3–312.8] vs. 0.22 [0.12–0.42] pg/ml, P <.0001) and T-cell proliferation (2.22 [1.18–7.56] % vs. 0.002 [0.001–0.11] %, P <.0001), suggesting recovery of VZV-specific CMI. Interestingly, VZV responders had a significant fold increase in ifn-γ gene expression, whereas ifn-γ mRNA was not detected in whole blood of VZV-non-responders (P <.0001). This study is the first to suggest that measurement of ifn-γ gene expression in 24-h-stimulated whole blood could be an accurate test of VZV-specific CMI. The routine use of this immune functional assay to guide antiviral prophylaxis at an individual level remains to be evaluated.